PENGINJILAN TERHADAP MASYARAKAT PLURAL BERDASARKAN SURAT EFESUS - Erna Ngala; Veydy Yanto Mangantibe (Excelsis Deo: Jurnal Teologi, Misiologi, dan Pendidikan, 2021)
This article discusses evangelism to plural societies based on the epistle of ephesians. Evangelism is god’s program, design and work that bring for himself, people to fellowship, worship / praise and serve him in wholeness and harmony. Evangelism is established by god from eternity, because all things are designed by god from eternity in his omniscience and power in evangelism (eph. 1: 4-14). God wants his people to have fellowship with him, become his worshipers and serve him, the true god. The challenge in evangelism is that every religion is different, all religions have objects that are worshiped, therefore it will not be possible to be completely equated between one religion and another. Plural society equates christian faith with other beliefs by looking for loopholes to align christianity with other religions. The duty of the believer is to preach the gospel so that unbelievers hear and believe in the lord jesus and are saved, not compromising the gospel or juxtaposing christian faith with other beliefs. Keywords: Evangelism; Plural Society; Ephesians Letter  AbstrakArtikel ini membahasa mengenai penginjilan terhadap masyarakat plural berdasarkan surat Efesus. Penginjilan merupakan program, rancangan dan karya Allah yang membawa bagi diriNya sendiri suatu umat untuk bersekutu, menyembah/memuji dan melayani Dia dalam keutuhan dan keserasian. Penginjilan ditetapkan Allah sejak kekekalan, sebab segala sesuatu dirancang Allah dari kekal dalam kemahatahuanNya dan kuasaNya didalam penginjilan (Ef.  1:4-14). Allah menghendaki agar umatNya bersekutu dengan Dia, menjadi penyembahNya dan melayani Dia, Allah yang benar. Tantangan dalam penginjilan adalah setiap agama berbeda, semua agama memiliki objek yang disembah, oleh sebab itu tidak akan mungkin dapat disamakan secara keseluruhannya antara agama satu dengan yang lain. Masyarakat plural, menyamakan iman Kristen dengan kepercayaan lain dengan mencari celah untuk dapat menjajarkan kekristenan dengan keagamaan lain. Tugas dari orang percaya ialah memberitakan Injil agar orang-orang yang belum percaya mendengar dan menjadi percaya kepada Tuhan Yesus serta diselamatkan, bukan mengkompromikan Injil atau menjajarkan iman Kristen dengan kepercayaan lain. Kata Kunci: Penginjilan; Masyarakat Plural; Surat Efesus